The mediating role of knowledge management in e-business in Malaysia / Sabrinah Adam, Batiah Mahadi and Siti Aisyah Panatik@Abdul Rahman - Adam, Sabrinah; Mahadi, Batiah; Panatik@Abdul Rahman, Siti Aisyah (Universiti Teknologi MARA, Shah Alam: Accounting Research Institute (ARI), 2018)
This paper aims to investigate the mediating role of knowledge management (KM) in the relationship between entrepreneurial orientation (EO) and organizational performance of e-businesses in Malaysia. Althoughknowledge management (KM), entrepreneurial orientation (EO) and organizational performance are primarily studied in business organizations, these issues are still important for e-business. However, few attemptshave been made to investigate the relationship between KM and EO, particularly in the context of Malaysian e-businesses. The present study fills this research gap by examining the effects of KM towards EO and organizational performance of owner/founder e-businesses. A quantitative approach via a self-administered questionnaire was used. Structural equation modelling using partial least squares (PLS-SEM) was performed to test the hypotheses. The findings indicate that EO has a positive effect on KM and KM has a positive effect on organizational performance. An analysis of the indirect effects suggests that KM mediates the relationship between EO and organizational performance. The current findings strongly indicate that KM leads to more effective decision making in order to achieve better performance. The findings have implications for academics and practitioners.